Nowcasting employment in the euro area - Marta Bańbura; Irina Belousova; Katalin Bodnár; Máté Barnabás Tóth (European Central Bank (ECB), 2023)
Euro area labour market variables are published with a considerable lag, longer than in the case of real GDP. We develop a suite of models to provide a more timely estimate (nowcast) of euro area quarterly employment growth based on a broad range of monthly indicators. The suite includes a batch of different dynamic factor model and bridge equation specifications. We evaluate it in real time over 2013-2022 and find that (i) monthly indicators provide useful information for a timely assessment of employment developments with unemployment rates and sentiment indicators containing most of the relevant information, (ii) the performance of small-scale models is comparable to those based on a larger information set, (iii) the suite performs favourably compared to the Eurosystem/ECB staff macroeconomic projections, (iv) forecasting performance deteriorates temporarily at the initial stage of the COVID-19 pandemic period, but the models outperform the benchmarks again thereafter.
Keywords: C53; E24; E32; E37; 330; Forecasting; Real-Time Data; Mixed Frequency